Perception of Audit Expectation Gap: A Study on Business Students of Bangladesh - Reza, Mohammed Moin Uddin; Khatun, Asia (World Journal of Vocational Education and Training, 2020)
This study objects to probe the audit expectation gap (AEG) among the business students from different public and private universities of Bangladesh. The study tries to explore the perception about the auditors’ role and its deviation from the actual scenario contributing to an AEG. This article try to observe the extent of Business Students’ ability to understand audit responsibilities, duties and auditor’s role in preventing fraud and thus identify the concerns that lead to an expectation gap through a closed-ended structured questionnaire. Results indicate that satisfaction level of the respondent is low regarding the activities of auditors and they expect more engagement from them. Accurate attachment of international auditing rules, association with foreign firm and independence of audit engagement will be the probable solution to reduce this overall audit expectation gap. Moreover, respondent are highly acquainted with the fact that internal management and their overall strategic control for decision making is equally important to enhance the credibility of disclosed corporate information.